2022
DOI: 10.1111/nmo.14357
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen administration alters gastrointestinal motility in mice

Abstract: Background Tamoxifen is widely used for Cre‐estrogen receptor‐mediated genomic recombination in transgenic mouse models to mark cells for lineage tracing and to study gene function. However, recent studies have highlighted off‐target effects of tamoxifen in various tissues and cell types when used for induction of Cre recombination. Despite the widespread use of these transgenic Cre models to assess gastrointestinal (GI) function, the effect of tamoxifen exposure on GI motility has not been described. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A recent study showed that TAM administration induced changes in contractility in isolated colons in mice, especially an increase in the number of short contractions. 33 TAM was used in both groups in our study. However, we did not compare LFHA contractions in animals that were treated with TAM and that were untreated, as both Kit-ChR2(+) and Kit-ChR2(–) mice received the same TAM injection, which ensured comparable results in isometric force recordings between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that TAM administration induced changes in contractility in isolated colons in mice, especially an increase in the number of short contractions. 33 TAM was used in both groups in our study. However, we did not compare LFHA contractions in animals that were treated with TAM and that were untreated, as both Kit-ChR2(+) and Kit-ChR2(–) mice received the same TAM injection, which ensured comparable results in isometric force recordings between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that tamoxifen co-administration via chow can exacerbate tissue damage and increase gut dysfunction. Indeed, tamoxifen administration in mice and humans showed altered gastrointestinal motility ( 45 ) and tamoxifen-induced intestinal epithelial barrier damage ( 46 ), respectively. Therefore, tamoxifen administration should be controlled for the off-target effects of tamoxifen treatment in GI.…”
Section: Glial Purine Signaling In Acute Colitis As a Double-edged Sw...mentioning
confidence: 99%